Topologically Associated Domains Delineate Susceptibility to Somatic Hypermutation - Senigl, Filip; Maman, Yaakov; Dinesh, Ravi K; Alinikula, Jukka; Seth, Rashu B; Pecnova, Lubomira; Omer, Arina D; Rao, Suhas S P; Weisz, David; Buerstedde, Jean-Marie; Aiden, Erez Lieberman; Casellas, Rafael; et al. (Cell reports, 2019)
Somatic hypermutation (SHM) introduces point mutations into immunoglobulin (Ig) genes but also causes mutations in other parts of the genome. We have used lentiviral SHM reporter vectors to identify regions of the genome that are susceptible ("hot") and resistant ("cold") to SHM, revealing that SHM susceptibility and resistance are often properties of entire topologically associated domains (TADs). Comparison of hot and cold TADs reveals that while levels of transcription are equivalent, hot TADs are enriched for the cohesin loader NIPBL, super-enhancers, markers of paused/stalled RNA polymerase 2, and multiple important B cell transcription factors. We demonstrate that at least some hot TADs contain enhancers that possess SHM targeting activity and that insertion of a strong Ig SHM-targeting element into a cold TAD renders it hot. Our findings lead to a model for SHM susceptibility involving the cooperative action of cis-acting SHM targeting elements and the dynamic and architectural properties of TADs.
Keywords: somatic hypermutation; Plasmids; Male; mutace; cytidindeaminasa; RNA-polymerasa II; Cell Line, Tumor; HEK293 buňky; activation induced deaminase; RNA Polymerase II; Cytidine Deaminase; chromatin structure; Somatic Hypermutation, Immunoglobulin; HEK293 Cells; mužské pohlaví; zesilovače transkripce; topologically associated domain; lidé; Enhancer Elements, Genetic; Humans; plazmidy; somatická hypermutace imunoglobulinových genů; Mutation; Lentivirus; nádorové buněčné linie; chromatin loop extrusion; transcription factor